Usando a difração da luz como analogia para a compreensão da estrutura cristalina, determinada por raios X - Santos, Cinara Maria dos (2018)
The use of experimental activities in the classroom allows interest and development of skills, enabling better understanding of scientific concepts, as well as directing understanding about various aspects of science. In this perspective, this work proposes a didactic sequence that adopts investigative experimental activities as a methodology, through the approach of topics such as diffraction and interference, aiming at the construction of easily accessible didactic materials. The activities aim to discuss the determination of crystalline structures by X-ray diffraction, using as an analogy the diffraction of light. The didactic sequence was applied in four stages, constituted by nine classes, which were developed in a public school together with students of the third year of High School. The results obtained during the activities were evaluated using conceptual theory (MORTIMER; EL-HANI, 2014; MORTIMER, 2000) as a theoretical reference, searching for indications of the evolution of these conceptual profiles, regarding the concepts of crystalline structures.